2019
DOI: 10.1080/16549716.2019.1656452
|View full text |Cite
|
Sign up to set email alerts
|

The introduction of a paediatric nutrition support program led by a clinical dietitian at a low-resource hospital setting in Malawi

Abstract: In low- and middle-income countries, nutrition support strategies are often suboptimal or non-existent in hospital settings. This is further compounded by high rates of malnutrition in these countries. The first four dietitians graduated in Malawi in 2017 providing a new opportunity to build capacity to introduce nutrition support in an acute care setting. A paediatric nutrition support program was implemented at Queen Elizabeth Central Hospital (QECH) in Blantyre, Malawi including the hiring of a local dietit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In 2018, the Malawi government introduced two dietitians in tertiary level health facilities, yet the patient to dietitian ratio remains too large to cater for the population in need. It is also notable that qualitative research around a nutrition support program led by a dietitian at Queen Elizabeth Central Hospital in Blantyre showed that nurses and physicians who worked alongside the dietitian valued the role of nutrition support in improving quality of care [ 6 ].…”
Section: Challenges In Clinical Nutrition Carementioning
confidence: 99%
“…In 2018, the Malawi government introduced two dietitians in tertiary level health facilities, yet the patient to dietitian ratio remains too large to cater for the population in need. It is also notable that qualitative research around a nutrition support program led by a dietitian at Queen Elizabeth Central Hospital in Blantyre showed that nurses and physicians who worked alongside the dietitian valued the role of nutrition support in improving quality of care [ 6 ].…”
Section: Challenges In Clinical Nutrition Carementioning
confidence: 99%